FREQUENCY OF RAISED SERUM LACTATE DEHYDROGENASE IN PATIENTS WITH JAK2 POSITIVE POLYCYTHEMIA VERA - Shah, Syed Zubair; Raza, Naila; Irfan, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Serum Lactate Dehydrogenase (LDH) is an easily available bio marker used to determine prognosis in various Myeloproliferative Neoplasms (MPN). Its utility in Polycythemia Vera (PV) is yet to be accessed. The purpose of this study was to determine the frequency of raised serum LDH in patients with JAK2 V617F positive PV patients and its clinic-pathological association. Materials and methods: A cross-sectional study using non probability consecutive sampling was conducted at our institute from July 2018 to June 2019. Adult patients of either gender, newly diagnosed with JAK-2 V617F positive PV were included. Patients’ demographics, clinical characteristics and baseline CBC and LDH levels were analyzed. Stratification was done with regards to age, gender, diabetes mellitus, hypertension, splenomegaly and thrombosis to see the effect of these modifiers on patients with raised LDH by using Chi Square test. P value of ‰¤0.05 was considered as significant. Results: Forty patients were inducted in the study with male to female ratio of 2:1. Twenty two (55%) patients had raised LDH levels and showed significant association with diabetes mellitus (p=0.001), splenomegaly (p=0.001) and thrombosis (p=0.018). Conclusion: This study observed raised LDH levels in almost half of JAK2 V617F positive PV patients. It warrants a larger scale study and suggests the value of plasma LDH to be used as a future prognostic marker in PV. Keywords: Serum lactate dehydrogenase, PolycythemiaVera, Diabetes mellitus, hypertension, JAK 2 V617F mutation, Myeloproliferative Neoplasm, Pakistan.